Fatigue life enhancement by irradiation of 12Cr1MoV steel with a Zr+ ion beam. Mesoscale deformation and fracture - Panin S. V. Sergey Viktorovich; Vlasov I. V. Ilya Viktorovich; Sergeev V. P. Viktor Petrovich; Ovechkin B. B. Boris Borisovich; Marushchak P. O. Pavel Orestovich; Ramasubbu S. Sunder; Lyubutin P. S. Pavel Stepanovich; Titkov V. V. Vladimir Viktorovich (2015, 2015)
Title screen